A Bibliometric Analysis of Neonatal Pain Management Research From 2010 to 2022 - Liao, Ling; Wang, Ying ying; Cao, Ying; Tan, Min (Zeitschrift für Geburtshilfe und Neonatologie, 2023)
Background Research related to neonatal pain management has received increasing attention in recent years. Effective pain management contributes to the maintenance of the healthy physical and mental growth of the newborn. To better understand this research topic, we analyzed the current state of development in this field over the past thirteen years by bibliometric analysis and provide directions for future research.Methods Original articles were collected from the Web of Science Core Collection (WoSCC) between January 1, 2010, to December 31, 2022, the title and abstract clearly stating ‘neonatal pain management’ or its alternative search keywords. CiteSpace, VOSviewer, and the WoS analysis tool were used to analyze and present the data.Results A total of 967 articles met the inclusion criteria. Significant growth of the number of publications increased roughly fourfold from 2010 to 2022. Overall, the United States and Canada were the highest contributors to neonatal pain management research. Weak cooperation was observed in international research (developing and developed countries) and cross-institutional cooperation. Neonatal pain-related research was the most common focus. Pain education and interventions for parents and medical personnel have also received increasing attention recently.Conclusion The current study revealed that research in terms of publications on neonatal pain management has rapidly increased for more than the past ten years. Developed countries, especially the United States and Canada, were more concerned with this topic than developing countries. More international research and cross-institutional cooperation are required to promote the development of neonatal pain medicine in the future.
Keywords: neonates; pain; management; bibliometrics